2016
DOI: 10.1007/s00710-016-0464-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental constraints on the relative stabilities of the two systems monazite-(Ce) – allanite-(Ce) – fluorapatite and xenotime-(Y) – (Y,HREE)-rich epidote – (Y,HREE)-rich fluorapatite, in high Ca and Na-Ca environments under P-T conditions of 200–1000 MPa and 450–750 °C

Abstract: The relative stabilities of phases within the two systems monazite-(Ce)fluorapatiteallanite-(Ce) and xenotime-(Y)-(Y,HREE)-rich fluorapatite-(Y,HREE)-rich epidote have been tested experimentally as a function of pressure and temperature in systems roughly replicating granitic to pelitic composition with high and moderate bulk CaO/Na 2 O ratios over a wide range of P-T conditions from 200 to 1000 MPa and 450 to 750°C via four sets of experiments. These included (1) monazite-(Ce), labradorite, sanidine, biotite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 88 publications
3
24
0
1
Order By: Relevance
“…Harlov, 2011Harlov, , 2015Harlov et al, 2002Harlov et al, , 2005Harlov and Förster, 2003). Experimental results Budzyń et al, 2017) are consistent with natural observations that fluid activity is just as important as changes in P-T conditions for monazite breakdown reactions (Finger et al, 1998(Finger et al, , 2016Janots et al, 2008;Ondrejka et al, 2012Ondrejka et al, , 2016. The formation of monazite micro-inclusions in apatite may not be coeval with the breakdown of granoblastic monazite to apatite-allanite; the former may have been produced at different temperatures by fluids that were also responsible for monazite resetting at ca.…”
Section: Petrographic Considerations In Accessory Mineral Datingsupporting
confidence: 84%
“…Harlov, 2011Harlov, , 2015Harlov et al, 2002Harlov et al, , 2005Harlov and Förster, 2003). Experimental results Budzyń et al, 2017) are consistent with natural observations that fluid activity is just as important as changes in P-T conditions for monazite breakdown reactions (Finger et al, 1998(Finger et al, , 2016Janots et al, 2008;Ondrejka et al, 2012Ondrejka et al, , 2016. The formation of monazite micro-inclusions in apatite may not be coeval with the breakdown of granoblastic monazite to apatite-allanite; the former may have been produced at different temperatures by fluids that were also responsible for monazite resetting at ca.…”
Section: Petrographic Considerations In Accessory Mineral Datingsupporting
confidence: 84%
“…Finger and Krenn 2007;Holder et al 2015;Kohn et al 2005;Williams et al 2011) and laboratory experiments (e.g. Budzyń et al 2011Budzyń et al , 2017Harlov et al 2011;Seydoux-Guillaume et al 2012;Shazia et al 2015). No relationship between Group 3 and the other monazite populations are observed.…”
Section: Timing Of Events Recorded By Monazitementioning
confidence: 88%
“…The CaO contents of the britholite increased from~8.3 tõ 13.8% with temperature, indicating a higher fluo-rapatite component in britholite. Similarly, Budzyń et al (2017) reported increasing REE contents from~30 to 40% in fluorapatite with increasing temperature from 450 to 750 8C. Anenburg & Mavrogenes (2018) showed that an appreciable solid solution between fluorapatite and britholite is only observed at 700 8C and above, and two immiscible phases occur at lower temperatures.…”
Section: Symplectite Formationmentioning
confidence: 89%